Alcohol-induced plasticity in the dynorphin/kappa-opioid receptor system - Sirohi, Sunil; Bakalkin, Georgy; Walker, Brendan M. (Frontiers in Molecular Neuroscience, 2012)
Alcoholism is a chronic relapsing disorder characterized by continued alcohol use despite numerous adverse consequences. Alcohol has been shown to interact with numerous neurotransmitter systems to exert its pharmacological effects. The endogenous opioid system (EOS) has been strongly implicated in the positive and negative reinforcing effects of alcohol. Traditionally recognized as dysphoric/anhedonic in nature, the dynorphin/kappa-opioid receptor (DYN/KOR) system has recently received considerable attention due to evidence suggesting that an upregulated DYN/KOR system may be a critical contributor to the complex factors that result in escalated alcohol consumption once dependent. The present review will discuss alcohol-induced plasticity in the DYN/KOR system and how these neuroadaptations could contribute to excessive alcohol seeking and consumption.